Hubungan Pola Asuh Orangtua dengan Kemandirian ADL (Activity Of Daily Living) Anak Tunagrahita Sedang di SLB N Purwosari Kudus - Oneivio Ananta Petra; hartini, sri; Biyanti Dwi W (Indonesian Journal of Nursing Research (IJNR), 2023)
Children with mental retardation have abnormalities in terms of intelligence which are characterized by limited intelligence, inability to interact socially and obstacles in the development of independence. One of the factors that influence the independence of mentally retarded children is from parenting, where parents have an important role in growing children's independence by providing parenting patterns that are in accordance with the child's potential. The purpose of this study was to determine the relationship between parenting patterns and the independence of ADL (Activity of Daily Living) for moderately retarded mentally retarded children at SLB N Purwosari Kudus. This study uses a quantitative correlation method with a cross sectional approach. The data used by parents and children with moderate mental retardation at SLB N Purwosari Kudus in 2021/2022. The sample technique used in this research is purposive sample with 44 respondents. Data analysis in this study used the Chi-Square test calculation. Parents who apply well parenting with the level of independence of independent children as many as 7 children, poor parenting with the independence of independent children as many as 25 children and bad parenting with the category of less independent independence as many as 2 children. From the Chi-Square test, the p value was 0.016 (p<0.05). There is a relationship between parenting style and ADL (Activity of Daily Living) independence for moderately mentally retarded children at SLB N Purwosari Kudus.   Abstrak Anak tunagrahita memiliki dependensi dari segi kecerdasan yang ditandai dengan keterbatasan intelegensi, ketidakmampuan dalam berinteraksi sosial dan hambatan dalam perkembangan untuk melakukan kemandirian. Salah satu faktor yang mempengaruhi kemandirian anak tunagrahita adalah dari pola asuh orang tua, dimana orang tua mempunyai peranan penting dalam menumbuhkan kemandirian anak dengan memberikan pola asuh yang sesuai dengan potensi anak. Tujuan Penelitian ini untuk mengetahui adanya hubungan pola asuh orang tua dengan kemandirian ADL (Activity of Daily Living) anak tunagrahita sedang di SLB N Purwosari Kudus. Penelitian ini menggunakan metode kuantitatif korelasi dengan pendekatan cross sectional (pendekatan silang). data yang digunakan yaitu data orang tua dan anak tunagrahita sedang di SLB N Purwosari Kudus tahun 2021/2022. Teknik sampling yang digunakan dalam penelitian ini yaitu purposive sampling dengan 44 responden. Analisis data pada penelitian ini menggunaka perhitungan uji Chi-Square. Hasil Orang tua yang menerapkan pola asuh baik dengan tingkat kemandirian anak mandiri sebanyak 7 anak, pola asuh kurang baik dengan kemandirian anak yang mandiri sebanyak 25 anak dan pola asuh tidak baik dengan kategori kemandirian kurang mandiri sebanyak 2 anak. Dari uji Chi-Square didapatkan hasil p value 0,016 (p<0,05). Terdapat hubungan pola asuh orang tua dengan kemandirian ADL (Activity of Daily Living) anak tunagrahita sedang di SLB N Purwosari Kudus.